Engineering design graphics: autocad, release 12. - James Earle
Introduction to engineering and technology. The design Process 15. Problem identification 27. Preliminary ideas 34..Idea Refinement 43. Desing Analysis 51. Decision 66. Implementation 78. Design Problem 93. Drawing Instruments 108. Lettering 128. Geometric Construction 138. Orthographic Sketching 166.Ortographic drawing with instruments 185. Auxiliary View 216. Sections 235. Screws, Fasteners, and springs 255. Gears and cams 287. Materials and Proceesses 301. Dimensioning 319. Tolerances 350. Welding 385. Working Drawings 395. Reproduction of drawings 447. Three-Dimensional Pictorials 452. Points, Lines, and Planes 481. Primary auxilliary Views in descriptive geometry 495. Successive auxiliary View 525. Revolution 539. Vector Graphics 553. Intersections and developments 568. Graphs 593